Process evaluation in practice based research networks: a study protocol for a mixed-methods implementation study - Sanftenberg, Linda; Dreischulte, Tobias; Härdtlein, Annette; Kosub, Helena; Gagyor, Ildiko; Kurotschka, Peter Konstantin; Kühlein, Thomas; Burggraf, Larissa; Eck, Stefanie; Roos, Marco; Gensichen, Jochen (BMJ Open, 2023)
INTRODUCTION: General practitioners often criticise clinical trials for their poor applicability in primary care, which may at least partially explain why their engagement in primary care research remains limited. In order to enhance primary care research, the German government has funded six regional practice based research networks (PBRNs). Within the Bavarian PBRN (BayFoNet), two cluster-randomised pilot trials will be conducted. This paper presents the protocol of the process evaluation accompanying both trials, which aims to explore relevance, feasibility, acceptability and credibility of clinical research in primary care from the perspectives of BayFoNet researchers, general practitioners, and patients. METHODS AND ANALYSIS: The BayFoNet will be established by recruiting general practices (GPs) as prospective research collaborators in two cluster randomised pilot trials. Research teams will provide training in good clinical practice, and support practices in patient recruitment, data collection and documentation. Our process evaluation explores barriers and facilitators in the set up of the BayFoNet PBRN and both cluster randomised pilot trials, under the application of the consolidated framework for implementation research and the theoretical domains framework. In a mixed-methods concept, we will use qualitative and quantitative approaches to evaluate both pilot cluster-randomised trials as well as the BayFoNet itself: focus groups with researchers, semi-structured interviews with general practitioners and questionnaires for patients participating in the pilot cluster-randomised trials at three different time points. ETHICS AND DISSEMINATION: Research ethical approval for this study was granted by the Ethics Committee of the Medical Department, Ludwig-Maximilians-University Munich (AZ 21-1135). Results will be published in international peer-reviewed journals and summaries will be provided to the funders of the study as well as other PBRNs, GP teams and patients. TRIAL REGISTRATION NUMBERS: DRKS00028805, NCT05667207.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Clinical Trial; GENERAL MEDICINE (see Internal Medicine); PRIMARY CARE; QUALITATIVE RESEARCH